An Investigation on Urban Circle Rail Transit: A Case Study on the Alignment of Mass Rapid Transit 3 (Circle Line) - A. A., Mohamed; E. J., Wei; Putra Jaya, Ramadhansyah; M. A., Farooqi; M. K. I. M., Satar; Nordiana, Mashros (IOP Publishing, 2020)
Mass Rapid Transit (MRT) is one of the important components of the Greater Kuala Lumpur (KL) development plan. It consists of three line-systems and would be finally operated by Klang valley public transport system. These three lines are aligned on the concept of wheel and spoke pattern that encompasses two north-south radial lines as well as a circular line (also known as ring line) circulating around KL and enclosing the central business district. However, fixing the locations of the stations has become an issue. The aim of the paper is to find out the optimal alignment for the ring line with respect to the total passenger benefit. A numerical-analytical model has been used to determine the optimum radius for the proposed ring line in a city. Passenger route choice for many-to-many, origin-destination (OD) pairs is analysed using radial-only rail network and rail network with ring lines of varying radii. The route choice takes into consideration three separate options including a) direct access to destination, b) taking only radial lines, and c) taking a combination of radial and ring lines. Several important parameters such as access cost, ride cost, and transfer penalty, are the main aspects to evaluate the optimality of the ring line. Microsoft Excel has been used to run the cost-benefit optimization model with the aim of obtaining an optimal radius of ring line. Results show that the net benefit of presenting a circle line in the KL by manipulating the passenger's cost for each OD pair. Finally, the optimum alignment of MRT circle line in KL has been proposed.